Taxonomy of the Afrotropical genera Angolositus Koch, 1955 and Pseudoselinus Iwan, 2002 with a key to species (Coleoptera: Tenebrionidae: Pedinini) - Kamiński, Marcin Jan (Zootaxa, 2012)
The validity of the genera Angolositus and Pseudoselinus is confirmed. The results of a comparative morphological analysis show that these two genera are closely related. One new species is described (Angolositus lidiae sp. n.) and Pseudoselinus elevatus is transferred into the genus Angolositus. Distributional maps are presented with complete faunistic data for the studied genera. An identification key is provided to all known species of Angolositus and Pseudoselinus.